The Role of Activator E2fs In Adult Neural Stem Cell Quiescence and Activation - O'Neil, Daniel (Université d'Ottawa / University of Ottawa, 2022)
Within the adult mammalian brain, Neural Stem Cell (NSC)s are maintained in distinct neurogenic niches in a mostly quiescent state. Activation of quiescent NSCs first requires re-entry into the cell cycle in order for the pool to proliferate and eventually commit to a neural fate, giving rise to newborn neurons. The canonical Retinoblastoma (Rb)-E2 Promoter Binding Factor (E2f) pathway is not only key in overcoming the Gap 1 Phase (G1)/S-phase restriction, but novelly appears to be involved in adult neurogenesis and NSC activation. I hypothesized that activator transcription factors E2 Promoter Binding Factor 1 (E2f1) and E2 Promoter Binding Factor 3 (E2f3) are crucial for exit from a quiescent state in adult NSCs. The contribution of the activator E2fs in this transition was studied using a Nestin-driven Cre Recombinase-Estrogen Receptor Tamoxifen-2 Ligand Binding Domain (Cre-ERT2) system to induce targeted deletion of E2f1/3 within NSCs in adult mice. We show that loss of E2f1/3 causes significant neurogenic defects, including pro-neural activation and decreased pools of adult NSCs, that preferentially adopt a quiescent profile in the subventricular zone. We employed this model to further isolate subventricular zone-derived NSCs using a Rosa26:Yellow Fluorescent Protein (YFP) reporter and subsequently analysed transcriptional profiles by RNA sequencing. Loss of E2f1/3 shifts NSC transcriptomes towards one overlapping with quiescent neural stem cell signatures (Codega et al., 2014; Basak et al., 2018), further highlighting the requirement of these E2fs for initial activation. A significant portion of these differentially expressed genes are putative E2f targets. Transcriptionally, major pathways involving cell metabolism, cellular signaling, and neural development are perturbed without activator E2f expression. In effect, this combined approach based on in vivo data and bioinformatics analyses offers a method of prospective identification of novel regulators of adult neurogenesis that require the activator E2fs. Preliminary data suggests that AT-Hook Transcription Factor (Akna) is one such target worth pursuing. Cumulatively, this project describes a unique role for E2f1 and E2f3 during NSC exit from quiescence and subsequent activation towards differentiation. As ongoing maintenance of quiescent NSCs is a necessary prerequisite for lifelong neurogenesis, conclusions from this study could determine the therapeutic potential of targeting activator E2fs to combat the niche exhaustion associated with aging, injury, and neurodegenerative diseases.
Keywords: e2f; neural stem cell; quiescence; cell cycle; activation; neurogenesis